2017
DOI: 10.1038/s41598-017-06620-2
|View full text |Cite
|
Sign up to set email alerts
|

Host seeking parasitic nematodes use specific odors to assess host resources

Abstract: Entomopathogenic nematodes (EPNs) are insect parasites used as biological control agents. Free-living infective juveniles (IJs) of EPNs employ host-seeking behaviors to locate suitable hosts for infection. We found that EPNs can differentiate between naïve and infected hosts, and that host attractiveness changes over time in a species-specific manner. We used solid-phase microextraction and gas chromatography/mass spectrometry to identify volatile chemical cues that may relay information about a potential host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 53 publications
7
60
0
Order By: Relevance
“…Trimethylamine (TMA) is associated with house crickets and pillbugs and is reportedly a neutral odor, neither attractive nor repulsive to S. carpocapsae IJs (Dillman et al, 2012). Prenol was recently identified as being associated with waxworms infected by EPNs and elicits a repulsive response from S. carpocapsae IJs (Baiocchi et al, 2017). We found that stimulating IJs by physical contact with waxworm cuticle did not significantly affect the chemotactic behavioral response or valence to any of the four host-associated odors -which were tested individually (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Trimethylamine (TMA) is associated with house crickets and pillbugs and is reportedly a neutral odor, neither attractive nor repulsive to S. carpocapsae IJs (Dillman et al, 2012). Prenol was recently identified as being associated with waxworms infected by EPNs and elicits a repulsive response from S. carpocapsae IJs (Baiocchi et al, 2017). We found that stimulating IJs by physical contact with waxworm cuticle did not significantly affect the chemotactic behavioral response or valence to any of the four host-associated odors -which were tested individually (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…The majority of S. carpocapsae IJs do not actively engage in host-seeking chemotaxis behavior, even in the presence of host odors (Gaugler et al, 1990;Lewis et al, 1992;Campbell and Gaugler, 1993;Lewis et al, 1995Lewis et al, , 1996Bal et al, 2014;Baiocchi et al, 2017). S. carpocapsae IJs spend a great deal of their foraging time performing tail standing -which lifts them from the substrate and allows them to perform jumping behavior -however, their foraging behavior can vary with their environment (Wilson et al, 2012;Kapranas et al, 2017;Hiltpold and Hibbard, 2018).…”
mentioning
confidence: 99%
“…There is growing evidence that chemosensory and other sensory modalities play an important role in nematode parasite transmission and intra-host migration (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . However, most studies have focused on single-host nematode parasites with direct life cycles, which are phylogenetically distant from the vector-borne filarial parasites of clade III.…”
Section: Introductionmentioning
confidence: 99%
“…Each amphid neuron expresses a diverse array of GPCRs, in contrast to the one-receptor-per-cell model in vertebrates (31)(32)(33) . These pathways have likely evolved to reflect the diversity of nematode life-history traits and environmental cues encountered by different parasite species (12,(17)(18)(19) . Despite superficial conservation of nematode chemosensory pathways, we hypothesized that there are important differences in chemosensory gene repertoire, patterns of expression, and function among free-living, single-host, and vector-borne parasitic nematodes belonging to diverse clades.…”
Section: Introductionmentioning
confidence: 99%
“…In the soil environment, the nematodes exist as infective juveniles (IJs) that carry the bacterial symbionts between insects (Poinar and Thomas, 1966;Martens et al, 2003;Herbert and Goodrich-Blair, 2007). IJs locate and infect an insect and within the insect body cavity undergo a recovery process to release their bacterial symbiont and enter the reproductive life stages (Sicard et al, 2004a;Snyder et al, 2007;Baiocchi et al, 2017). The nematodes and bacteria then kill the insect host and grow within the cadaver [reviewed in (Herbert and Goodrich-Blair, 2007;Richards and Goodrich-Blair, 2010)].…”
Section: Introductionmentioning
confidence: 99%